Love That Produces Hope : The Thought of Ignacio Ellacuría - Lassalle-Klein, Robert Anthony; Burke, Kevin F.; Aquino, María Pilar (Book collections on Project MUSE., 2006)
"Father Ignacio Ellacuria, SJ, president of the University of Central America, leading Latin American philosopher, and liberation theologian, was assassinated with five Jesuit companions and two women on November 16, 1989. Love That Produces Hope brings together leading authorities on key aspects of Ellacuria's thought. The book introduces readers to the groundbreaking life and thought of Ignacio Ellacuria. His biography and writings embody late twentieth-century transformations and tensions that reshaped the life of the Catholic church among the crucified peoples of Central America. Love That Produces Hope evaluates the significance of Ellacuria's work, particularly his impact on theology, philosophy, and education. Ellacuria found hope in his faith that God's grace sustains the tenacious struggle of millions of men, women, and children to nurture those they love in the face of poverty and an uncertain future."--Publisher's website.